2020
DOI: 10.1007/s10549-020-05769-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision trees support systematic evaluation of multidisciplinary team recommendations

Abstract: Purpose EUSOMA's recommendation that "each patient has to be fully informed about each step in the diagnostic and therapeutic pathway" could be supported by guideline-based clinical decision trees (CDTs). The Dutch breast cancer guideline has been modeled into CDTs (www.oncog uide.nl). Prerequisites for adequate CDT usage are availability of necessary patient data at the time of decision-making and to consider all possible treatment alternatives provided in the CDT. Methods This retrospective single-center stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
5
1
1
Order By: Relevance
“…An unconditional recommendation from a CDT depends on availability of complete data. In this study, data availability per case was higher than previously reported [ 11 , 12 , 18 ]. The systematic application of a CDT uncovers the amount of missing data required for guideline-based decision-making and thereby may stimulate a more complete reporting of necessary data.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…An unconditional recommendation from a CDT depends on availability of complete data. In this study, data availability per case was higher than previously reported [ 11 , 12 , 18 ]. The systematic application of a CDT uncovers the amount of missing data required for guideline-based decision-making and thereby may stimulate a more complete reporting of necessary data.…”
Section: Discussioncontrasting
confidence: 68%
“…To date, CDTs were evaluated on validity for usage in MDTs retrospectively by Hendriks et al. [ 11 ] for breast cancer and by Keikes et al. [ 12 ] for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, a formação de uma equipe multidisciplinar oferece muitas vantagens, como um diagnóstico mais preciso, menor tempo do diagnóstico ao tratamento, maior probabilidade de administrar todos os tratamentos, melhor comunicação de todos os membros e maior suporte para o manejo do paciente, mas a transferência parcial de seus trabalhos para o meio virtual pode causar um impacto em suas demandas, já que a implementação do mesmo ocorreu em caráter emergencial. (HENDRIKS et al, 2020).…”
Section: Introductionunclassified
“…A Dutch clinical decision support system incorporates the recommendations of the European Society of BC Specialists (EUSOMA), each patient has to be fully informed about each step in the diagnostic and therapeutic pathway and must be given adequate time to consider the alternatives and make an informed decision. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…each patient has to be fully informed about each step in the diagnostic and therapeutic pathway and must be given adequate time to consider the alternatives and make an informed decision. 26 , 27 …”
Section: Introductionmentioning
confidence: 99%